Revision of Scheumann’s classification of melilitic lamprophyres and related melilitic rocks in light of new analytical data - Ulrych,J.; Adamovic,J.; Krmicek,L.; Ackerman,L.; Balogh,K. (Journal of Geosciences, 2014)
Dykes of the Late Cretaceous to Early Tertiary (79.5 ± 3.5 to 60.7 ± 2.4 Ma) melilitic rock series of the Osecna Complex and the Devil’s Walls dyke swarm, including ultramafic lamprophyres - polzenites - of Scheumann (1913) occur dispersed in the entire Upper Ploucnice River basin in northern Bohemia. Polzenites and associated melilitic rocks are characterized by the mineral association of olivine + melilite ± nepheline, haüyne, monticellite, phlogopite, calcite, perovskite, spinels and apatite. New data on their mineral and chemical compositions from original Scheumann’s localities (the Vesec, Modlibohov, Luhov types) argue against the abolition of the group of ultramafic lamprophyres and the terms ‘polzenite’ and ‘alnöite’ by the Le Maitre (2002) classification. Marginal facies and numerous flat apophyses of the lopolith-like body known as the Osecna Complex show an olivine micro-melilitolite composition (lamprophyric facies). The porphyritic texture, chemical composition and the presence of characteristic minerals such as monticellite and phlogopite point to their affinity with ultramafic lamprophyres - polzenites of the Vesec type. Melilite-bearing olivine nephelinites to olivine melilitites (olivine + clinopyroxene + nepheline + melilite ± haüyne and spinels with apatite) form a swarm of subparallel dykes known as the Devil’s Walls. The Scheumann’s non-melilite dyke rock “wesselite”, spatially associated with polzenites and often erroneously attributed to the polzenite group, is an alkaline lamprophyre of monchiquite to camptonite composition (kaersutite + phlogopite + diopside + olivine phenocrysts in groundmass containing clinopyroxene, phlogopite, haüyne, analcime, titanian magnetite, apatite ± glass/plagioclase). First K-Ar data show Oligocene ages (30.9 ± 1.2 to 27.8 ± 1.1 Ma) and an affinity to the common tephrite-basanite rock series.
Keywords: melilitic rocks; lamprophyres; polzenites; classification; geochemistry; Bohemian Massif